RUSSIA’S INTERESTS AND ROLE IN THE ESTABLISHMENT OF THE KINGDOM OF THE NETHERLANDS: THE DYNASTIC UNION WITH THE HOUSE OF ORANGE AS AN INSTRUMENT OF FOREIGN POLICY UNDER ALEXANDER I - Y. V. Bavykin (Vestnik MGIMO-Universiteta)
In the late 18th and early 19th centuries Europe was largely influenced by the French Revolution, which appeared as a major blow to the Westphalian political system. Motivated by its revolutionary ideas with the aim to spread them throughout Europe, to confirm its political and economic hegemony on the continent, the First French Republic and later the First Napoleonic Empire during its numerous wars conquered and controlled most of western countries, including the Netherlands, which later also became a satellite state of France. As a major opponent of France’s aggressive policy of that period and Napoleon’s defeater, Russia and its Emperor Alexander I took a significant part in the postwar settlement of Europe. However, Russia’s key role in liberating European countries, among which the Netherlands, from France’s oppression and in establishing their independence is often omitted and ignored in western historiography. By using archival documents, including Dutch ones, the author’s purpose is to show that due largely to consistent policy of Alexander I towards restoring independence of the Netherlands, in full accordance with Russia’s national interests, to the Emperor Alexander’s personal participation at the Congress of Vienna, a new state was formed in 1815 – the United Kingdom of the Netherlands. An essential instrument of Emperor Alexander’s foreign policy which strengthened the ties between the two countries was the dynastic marriage in February of 1816 of his younger sister Grand Duchess Anna Pavlovna with Dutch Hereditary Prince of Orange William who became in 1840 the King of the Netherlands William II.